Peranan Procedural Justice sebagai Mediasi antara Personality dengan Citizenship Behavior toward Environment Siswa - Balqis Wahyu Utami; I Made Putrawan; Ade Suryanda (IJEEM - Indonesian Journal of Environmental Education and Management, 2021)
This research was aimed at finding out the effect of Personality on students’ Citizenship Behavior Toward Environment mediated by Procedural Justice. The method used is causal survey by selecting 74 junior high school students in Jakarta randomly. There were four instruments measured, Personality (25 items with a reliability coefficient .859), Procedural Justice (24 items with a reliability coefficient .866), and Citizenship Behavior Toward Environment (26 items with a reliability coefficient .875). Data analyzed by path analysis. The research results showed that Personality and Procedural Justice directly and significantly affected Citizenship Behavior Toward Environment, Personality directly and significantly affected Procedural Justice, then Personality indirectly and significantly affected on Citizenship Behavior Toward Environment mediated by Procedural Justice. Therefore, it can be interpreted that Procedural Justice was a good mediator. Based on those results, it could be concluded that if students’ Citizenship Behavior Toward Environment would like to be improved positively, it’s should be minimized the variations factors such as personality and procedural justice by introducing and implementing procedurally fair environmental education, especially during the pandemic.